Unveiling new horizons in severe aplastic anemia management: a two-decade study on intensive immunosuppressive therapy combined with unrelated cord blood efficacy - Li, Zhipeng; Yu, Xiaolin; Song, Xiaochen; Li, Wenjun; Deng, Lei; Kong, Fanjun; Wang, Jing; Ni, Meiling; Zhou, Fang (Frontiers in Immunology, 2025)
BackgroundIn the absence of a human leukocyte antigen (HLA)-matched donor, intensive immunosuppressive therapy (IST) combined with unrelated cord blood (IIST-UCB) a salvage treatment option for patients with severe aplastic anemia (SAA) who had failed IST. With advancements in transplantation technology, outcomes of IIST-UCB have improved considerably in recent years. Here, we will focus on the differential effects of IIST-UCB on patient survival and GVHD risk and evaluate its therapeutic efficacy between SAA and VSAA patients.MethodsBetween August 2004 and May 2024, 115 SAA patients were screened at enrollment. The overall survival (OS) rates and failure-free survival (FFS) rates were evaluated and compared using Kaplan–Meier curves and log-rank tests. Cumulative incidences of cytomegalovirus (CMV), hematopoietic recovery, and Epstein–Barr virus (EBV) were estimated using a competing risk regression model.ResultsThe median age was 16 years (range, 2–74). At 6 months, 27 patients (27%) achieved complete response (CR), and 44 patients (44%) achieved partial response (PR). The median period to neutrophil engraftment was 25 days, and to platelet engraftment was 44 days. The 250-day cumulative incidence of hemoglobin recovery was 87.8% (95% CI, 77.7%–93.6%). The 100-day cumulative incidence of neutrophil engraftment was 88.5% (95%CI, 80.6%–93.3%). The 400-day cumulative incidences of platelet engraftment was 86.7% (95%CI, 77.5%–92.4%). The 5-year overall survival was 86.1% ± 6.66%, and the 5-year failure-free survival was 72% ± 8.62% in the cohort. Transplantation-related mortality was 12.5% (95% CI, 7.2%–19.4%). No acute or chronic graft-versus-host disease (GVHD) was observed during the entire period. The cumulative incidences of CMV and EBV were 7.18% (95% CI, 3.34%–13%) and 16.8 (95% CI, 10.6%–24.3%), respectively. The majority of patients exhibited microchimerism and maintained hematopoiesis over the long term. Patients with SAA who received UCB treatment showed significantly higher hematopoietic reconstitution efficiency (P = 0.004, P = 0.001, P = 0.001) and overall survival compared with the VSAA group (P = 0.028).ConclusionThese data support IIST-UCB as an alternative therapeutic approach for patients with SAA.